Godsdiensopvoeding op skool - enkele aannames in die konsepbeleid - Snyman, AH (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
At the beginning of April 2003 the Department of Education released its draft policy on religion in education for comment. The policy is based on certain ideological assumptions about the relation between state and school, neutrality and neutral religion education, value-free education, the relation between values and religion, as well as between multiculturality and religious diversity. These assumptions have been addressed by commentators in newspapers and other public media, but in a sporadic and often uncritical way.